Development of Integrated Learning Tools for Character Values in Science Subjects in Junior High School - Monita, Monita; Asyhar, Rayandra; Murni, Pinta (Integrated Science Education Journal, 2024)
Purpose of the study: The purpose of this study is to provide learning tools along with Student Worksheets that are integrated with character values, to determine student responses to Student Worksheets contained in learning tools, and to determine the effectiveness of Student Worksheets. Methodology: The development procedures used are ADDIE, Analysis, Design, Development, Implement, Evaluate, with a research design of one group pretest-postest design. The sample of the study was 33 grade VIII students, Junior High school 17 Jambi City. The instruments used are questionnaires, observation sheets of teacher and student needs, and documentation. The instruments used are obtained by adaptation. Main Findings: The results of the teacher's response obtained an average score of 4 with a good category and the results of the average student response of 4.2 with a good category. The validation results of material experts and media experts were 3.9, Good category and 4.5, Very Good category, respectively Novelty/Originality of this study: This research integrates character values into a learning tool equipped with Student Worksheets. From this research will help readers to know how to integrate character values into a learning tool.